Penggunaan Owabi Hyougen sebagai Tuturan Direktif Permintaan pada Zaman Edo dalam Manga One Piece - Wandari, Khalilla Putri; Yuliani Giri, , Ni Luh Kade; Indra Pradhana, Ngurah (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study entitled "The Use of Owabi Hyougen as Directive Speech Acts in the Edo Period in the Manga One Piece," aims to analyze the function of owabi hyougen as directive speech acts and the factors behind their use. This research employs a pragmatic approach with Searle's speech act theory and Brown and Levinson's politeness theory. The method applied is contextual analysis, with results presented informally. Based on the findings in the manga One Piece, it is revealed that directive speech acts are used to request help, information, and to ask others to do something. The use of owabi hyougen in this study is influenced by factors of distance, power, and rank of imposition, depending on the positions of the speaker, the listener, and the situation. The most dominant factor influencing the use of owabi hyougen in this study is distance, which indicates the social relationship or gap between the speaker and the listener.